Perancangan dan Implementasi Query Data Extractor Berbasis Remote Method-Invocation - Eddy Maryanto; Teguh Cahyono; Nur Chasanah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
Distributed databases have been a research subject that attracted many researchers to study. Distributed databases have many advantages, such as reliability and data availability. There are still many problems in this subject area that need to be solved through researches. In this paper, query data extractor, a subsystem of distributed database system, is designed and implemented. Query data extractor reside at the heart of the distributed database system. The main task of the query data extractor is to extract query data issued by applications sitting at a site to result data needed by optimizer subsystem in fragmentation and allocation processes.